Knowledge, Attitudes and Practice of Burns Prevention and First Aid among Medical Students of King Khalid University, Saudi Arabia (Bangladesh Journal of Medical Science, 2018)
Background: Burn prevention and first aid knowledge amongst medical students is a neglected subject.Objectives: 1.Assess the knowledge, attitudes and practices of medical students regarding burn prevention and first aid 2. Identify their sources of knowledge.Materials and Methods: This cross-sectional survey of KKU medical students documented their sociodemographic data, knowledge, attitudes and practices of burn prevention and first aid, and their sources of information. Data was analysed using SPSS 17. Descriptive information was presented as frequency and percentages, while Chi square test was used to find association of knowledge with sociodemographic factors.Results: A total of 273 students, from preclinical and clinical level were enrolled in the study. With an average of 9.3 correct responses, the median score of knowledge regarding burn prevention and first aid was 56.2 %. About half of the respondents (50.9%) achieved a fair knowledge score i.e. between 50-75%.College curriculum emerged as the major source of information for burn prevention (34.06%) and first aid (25.27%). About 42 % students suggested that inclusion in college curriculum would be the best way to increase awareness. YouTube emerged as the most common extra-curricular learning method (67.7%). Students in clinical years of medical education demonstrated significantly higher knowledge than those in pre-clinical years (p=0.01, COR=1.82). Fire prevention practices were not widely in place; however students revealed a positive attitude towards the same.Conclusion: Medical students have a fair knowledge in burn prevention and first aid and carry a positive attitude towards training. Incorporating social media for health awareness shows promise.Bangladesh Journal of Medical Science Vol.17(4) 2018 p.537-544